THE STRATEGY OF THE HEAD OF SMAIT IBNU ABBAS KLATEN SCHOOL IN INCREASING THE QUALITY AND ABSOLUTE OF GRADUATES AT STATE HIGHER EDUCATION - Kusyaeni; Pembangunan, Heldy Ramadhan Putra; Wardiyono, Kelik (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study was to analyze the strategy of the SMAIT Ibnu Abbas Klaten principal in improving the quality and absorption of graduates at state universities. This study uses a qualitative approach. Data collection techniques in the form of observation, interviews and documentation. The data analysis technique used in this research is interactive qualitative from Miles and Huberman which consists of data reduction, data presentation and drawing conclusions. The results of this study indicate that the head of SMAIT Ibnu Abbas Klaten has strategies including: (1) Set two targets, namely that graduets can enter the top 10 state universities based on the Times Higher Education World University Ranking (THE WUR) with an average score of 600 and based on the Computer-Based Written Examination by the Institute for Higher Education Entrance Tests (LTMPT); (2) Create and implement programs for the realization of goals, namely forming a success team for further studies, tutoring by internal teachers, involving professional staff, try outs, spiritual programs, mabit programs with parents, study tours to state universities, collaboration with private universities, teacher upgrading through in house training, teacher deliberations subjects and other associations; (3) The school principal conducts tiered evaluations through supervision of the vice principal of curriculum, student affairs and counseling guidance.